Comparative study of ordinary portland cement from different production (Al Fatiah and Al Huarry cement factories), NE Libya - Fares, F; Shaltami, O; Saad , Elebaidi; Mohamed, Fathi; El Gahmi, Mohammed (Libyan Journal of Science &Technology, 2022)
This study will discuss the evaluation of clinkers and cement powdered chemistry during manufacturing process from Al Fatiah and Al Huarry Cement Factories then matching with British standard. The bulk geochemical analysis has been carried out using X- ray fluorescence (XRF) and inductively coupled plasma-mass spectrometry (ICP-MS) techniques. The chemical analyses data showed that the limestone at the Al Fatiah Cement Quarry is classified as a high pure limestone and the limestone at the Al Huarry Cement Quarry is a low pure limestone. The studied terra rossa samples showed a suitable composition and could be a good source for SiO2 and Al2O3. The results of homogeneous samples of clinkers and cement powdered were compared to the British Standard.